Bahram and Golandam; A Narrative of the Process of Individualization - Mahdi Sharifian; Roya Hashemizadeh (Matn/Pizhūhī-i Adabī, 2024)
The relationship between literary texts and psychoanalysis was proposed in the 20th century with the help of Freud's theories, and after him, Carl Gustav Jung played a prominent role in this field and wrote important works about the reflection of people's emotions and thoughts in his creations. According to Jung, human thoughts are partly derived from daily desires and are largely influenced by the collective unconscious and old images (archetypes), and in general, humans are controlled by their unconscious throughout their lives. In this article, the epopee Bahram and Golandam by Aminuddin Safi (the poet of the 9th century) has been analyzed using the descriptive-analytical method and from Jung's psychoanalytic point of view in order to determine the level of collective unconsciousness and its elements in it. According to the obtained results, this folk tale is consistent with the archetype of Jung's individuation and shows the path of character development towards evolution; hence, in this poem, Keshvarshah is a code of humans and Bahram represents his archetype, who goes through the difficult stages of confronting the shadow to connect with the anima, and finally, his connection with Golandam completes the cycle of character transformation. Also, in this system, two archetypes of the shadow and the old man play a more prominent role: the archetype of the shadow due to the persistence and great effort of the king to develop the character, and the archetype of the old man due to his enthusiasm and confusion.Keywords: Jung, Archetype, Collective Unconscious, Aminuddin Safi, Bahram and Golandam. IntroductionAccording to Jung, the human psyche has three parts, which include the conscious mind (I or ego), the personal unconscious, and the collective unconscious. Jung defined the personal unconscious as a special area adjacent to the ego. He feels that a person's unconscious consists of ideas and emotions that existed as consciousness at one time; but now they are suppressed, forgotten, or for some reason purposefully ignored or forced out.The collective unconscious is the main part of the psyche and is much deeper and wider than the conscious part. This part of the psyche contains ancient images that are almost the same among all human beings and are reflected in dreams and other unconscious activities. Literature ReviewAccording to Jung, due to having a common mental structure, people face similar problems in different periods, and the key to solving these problems should be found with the help of collective and ancient psychological experiences. He called these old experiences archetypes and this term is the most important topic in his psychoanalysis.The contents of the collective unconscious are not acquired, but inherited, and thus are the same across cultures. This unconsciousness consists of two main aspects, i.e. archetypes and instincts (such as sexual instinct, violence, etc.). Archetypes are a reservoir and storehouse of experiences that have been constantly repeated throughout human history. These patterns always exist for every human being from birth and they have chosen a home in the deepest part of their unconscious. Every human being can face them internally through dreams and imaginations and externally through myths and religious teachings (Snowden, 2013: 121).Archetypal images or archetypes show different aspects of the mental apparatus and each one is revealed with the help of some symbols. Jung introduced some of their most important forms as follows: self, shadow, anima and animus, old man, mother, hero, mask, etc. In this article, our intention is to show the growth path of Keshvarshah's personality in the epopee of Bahram and Golandam. MethodologyThe book Bahram and Golandam is about the love of Bahram, the prince of Rome, to Golandam, the daughter of the Khaqan of China, and by reflecting on the structure of the story, its symbolic depth is determined. In fact, in this poem, the poet has symbolically told the story of the evolution and integration of the character with the help of a folk tale, and each of the elements of the story, such as characters, phenomena, and various creatures, are a symbol of a part of the unconscious mind, and Prince Bahram's battle to reach his lover, in the language of psychoanalysis, is a reflection of the psyche's sweating to solve problems related to the unconscious and absorb it into consciousness. ConclusionFolktales have a happy ending with a happy union. The same issue shows the repetitive pattern of these stories and, in fact, general and universal content that depicts the path of human excellence towards a comprehensive personality. In this research, the following results have been obtained:Keshvarshah is a symbol of man or the actualized dimension of the psyche (self-awareness) that strives to achieve a new and superior personality.Prince Bahram is a symbol of his archetype, which becomes active after man's effort and concern for progress and tries to harmonize different parts of the unconscious mind. At first, he reaches the psychic center with the help of an unseen helper (deer, a code of the wise old man) and there, after facing the image of his incomparable lover (Anima), with the guidance of the wise man (Pir Bazargan), he walks on the long and difficult path of love.In this story, the shadow has a positive side as well as a negative side. After encountering Anima, the prince reaches the land of fairies (Jenian). Jeni brothers (Shadow archetypes) first appear in the enemy's delegation and after defeating Bahram, they help him in the prince's battles by giving him a few strands of their hair; Therefore, after this change, they are considered a symbol of the positive dimension of the shadow. The negative effects of the shadow have also been shown by elements such as the prince's rivals and the demons, after defeating the Jenian, Bahram first faced the demon and after killing it, he faced the mysterious and terrifying world of the collective unconscious (the terrible sea) and the various manifestations of this unconscious, such as the negative shadow (Behzad and Noushadshah), the hero, etc.In the end, after marrying Golandam, Bahram finds out about his father's restlessness and unhappiness with the help of the archetype of sleep, and after returning to his homeland, he becomes a worthy successor to his father. In this story, the direction of the prince's journey is from the West, i.e. ignorance, to the East, i.e. inner illumination, and this is another secret of man's effort to achieve the higher aspect of personality. According to Jung's view, in this system, the prince's conflict is related to the negative aspects of the psyche; because it is difficult for humans to accept the negative aspects of their existence and to change them. The archetype of the wise old man also appears twice in the story, and the reason for this is the prince's confusion and desperate need to find a way out of his current situation.